MUSLIM CLERGY IN THE SOCIAL AND POLITICAL LIFE OF AFGHANISTAN - SIKOEV, Ruslan (CENTRAL ASIA AND THE CAUCASUS, 2006)
Afghanistan’s past greatly affects its present. This is especially true of the two state coups: the anti-monarchy coup of 1973, which brought Mohammad Daud to power, and the events of 1978, which brought the Marxist People’s Democratic Party of Afghanistan (PDPA) to power. They were followed by a protracted civil war and foreign military interference which consecutively created the regimes of the Islamic fundamentalist-mojahedin in 1992, which declared Afghanistan an Islamic state, and of the radical Taliban movement, which established a military theocratic regime in the form of the Islamic Emirate throughout most of the country. Late in 2001, it fell under blows delivered by the international U.S.-led counterterrorist coalition and the Northern Alliance. The nation paid dearly for the years of devastating internecine war with loss of life, destroyed political, economic, and cultural infrastructure, an altered demographic situation, and millions of émigrés. (According to the U.N., there are about three million Afghan refugees in Pakistan alone.1) The wars and the kaleidoscopic regimes delivered a crushing blow to the centuries-old moral and ethical norms and traditional lifestyle of the Afghans, as well as to their habits and customs. Islam as an important part of the local lifestyle was no exception; the war affected the situation of the Muslim clergy and the Islamic institutions. Under the Marxist regime of the PDPA, the clergy was persecuted and its members repressed. The anti-Islamic policy was especially cruel at the very beginning of the party’s rule, when the clans of Mojaddidi, Waezi, Qiyani, and other respected religious figures suffered a lot. Under the mojahedin and the Taliban, the clergy was brought to the very summit of power. The role of the clergy and its influence on the country’s contemporary life stem from the nation’s past. For a long time, between the 7th and 11th centuries, since the time when Islam finally established itself as the main religion of the local tribes, a multi-step social-economic hierarchy developed. It consisted of individual groups of clergies which differed in their level of material well-being and their influence on the popular masses. The ulamaye dini (the religious ulemas) occupied the highest steps of the structure. The group consisted of theologians—the maulawis, mudarisses-mutabahhirs (erudite persons), faqihs, etc. normally educated in the best Islamic centers abroad—Deoband in India, Al-Azhar in Egypt, and others. The official clergy was recruited from this group; its members sit in the Ulema Council, the Ihtisab (Islamic morality police), the Court, and the Ministry for Islamic Affairs and the Waqufs. As bureaucrats paid by the state and supporting its policy, these people were not hugely popular among the common people.